Der Markt fur̈ Milch - Marianne Kurzweil; Petra Salamon (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Milk MarketDifferent regional trends are seen world-wide with overall cow milk production further increasing at a moderate rate. World demand for dairy products suffered from retarded income growth and together with relatively rich supplies resulted in depressed world prices. Within the EU various measures were taken in favour of increased sales but neither subsidies on domestic consumption nor refunds on exports prevented intervention stocks from growing. Milk production having surpassed the quotas in 2001/02 only moderately is presently risking to see major excess quantities by the end of 2002/03.
Keywords: 330; Milchmarkt; Deutschland; EU-Staaten; Welt